The Effect of World Cafe Learning Method on Students’ Oral Communication Competence in Biology Learning - Frely Rahmawati; Aditya Rahman; Usman Usman (Gagasan Pendidikan Indonesia, 2021)
This study aimed to determine the effect of the World Cafe learning method on students' communication competence in biology learning on ecosystem concept. The method used in this study is a quasi-experimental method with a randomized control group only design. The research was conducted from September 2017 to October 2019. The research sample was class X IPA 6 and X IPA 3 which were taken by random sampling at one high school in Indonesia. The instruments used were observation sheets and test descriptions. The experimental and control classes have different results. This can be seen in the average scores of oral and written communication competence in the experimental class, respectively 80.6 and 70. Meanwhile, for oral and written communication competence, the control class scores respectively 74 and 54.8. The results of statistical tests on oral competence were 0.015 which were less than 0.05. So, it can be interpreted that the World Cafe learning method affects students' communication competence on ecosystem concept.